Minori soli nella migrazione. Esperienze di mobilità e di radicamento tra i confini - Elia, Anna (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2020)
The issue of the “unaccompained minors” is a structural component in the European scenario of the contemporary migrations. Still, the double representation of minor/immigrant it prevents, from one side, to read the complexity of this phenomenon and, from the other side, it tends to deprive these young people of every possibility to platy a role of social actors. The article, reporting the results of an empirical investigation carried out in Calabria, would stress the attention on the necessity to overturn this approach, starting from the observation of the interaction between the unaccompained minors who are alone and the “adults world” made of social workers, legal tutors, caregivers, educators, in their residential communities.